1976
DOI: 10.1677/joe.0.0680331
|View full text |Cite
|
Sign up to set email alerts
|

Egg Transport in Ovariectomized Rabbits as Affected by Different Combinations of Oestrogen and Progesterone

Abstract: A total of 1548 eggs was transferred to the oviducts of rabbits ovariectomized 45 days to 7 months earlier. The pattern of egg transport was disrupted, and the majority of eggs were in the vagina 60-72 h after transfer. To determine the role of the ovarian hormones on egg transport, the effects of various combinations of oestrogen and progesterone were studied. None of the hormonal treatments produced the normal transport pattern and large proportions of transferred eggs were retained in the oviducts. It is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, when comparing PTS in the ipsilateral ampullae of COD cows with control cows, it became obvious that cows with luteal cysts revealed significantly decreased PTS as compared with controls. It is possible that decreased (El-Banna & Sacher, 1976). However, previous reports of systemic serum progesterone levels are similar in diestrus cows (10-11 ng/ml) and cows with luteal cysts (8-9 ng/ml) (Brodzki et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…However, when comparing PTS in the ipsilateral ampullae of COD cows with control cows, it became obvious that cows with luteal cysts revealed significantly decreased PTS as compared with controls. It is possible that decreased (El-Banna & Sacher, 1976). However, previous reports of systemic serum progesterone levels are similar in diestrus cows (10-11 ng/ml) and cows with luteal cysts (8-9 ng/ml) (Brodzki et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Previous reports have shown that oocytes are transported very slowly through the isthmus as long as progesterone (P4) is the dominant hormone, and that a surge of E2 is required to modify the action of P4 and accelerate the transport of oocytes to the uterus. 35) Moreover, E2 reportedly stimulates myometrium contractility in nonpregnant humans. 36) The highest E2 concentration is observed during the follicular phase, and P4 increases in bovine oviducts after ovulation.…”
Section: Discussionmentioning
confidence: 99%